A curious case of adult with accidental mercury ingestion presenting as foreign body in gastrointestinal tractwith isolated central nervous system toxicity - Kamat, Manmohan Madhukar; Singh, Neeraj Pratap; Nattey, Kartik; Shetye, Shravani; Barman, Seema (Indian Journal of Case Reports, 2019)
Mercury is a heavy metal known for its toxicity and noted for inducing public health disasters in Minamata Bay, Japan, and Iraq. The toxic effects of mercury can either be acute and extremely severe or can manifest very subtly over a long period. Here, we report the case of a 56-year-old gentleman presented with complaints of sudden loss consciousness. On further evaluation and radiological examination, the patient had features suggestive of encephalopathy with a suspected foreign body in the gastrointestinal tract. Foreign body was found to be elemental mercury with elevated serum mercury levels. He was managed conservatively with chelation therapy with dimercaprol and prokinetic drugs such as polyethylene glycol which lead to the advancement of foreign body in the gastrointestinal tract on repeated abdominal x-rays with subsequent complete clearance.